Adsorption of phosphate onto amine functionalized nano-sized magnetic polymer adsorbents: mechanism and magnetic effects. Issue 28 (25th February 2015) - Shen, Haoyu; Wang, Zhejun; Zhou, Ameng; Chen, Junliang; Hu, Meiqin; Dong, Xinyan; Xia, Qinghua
Abstract : Tetraethylenepentamine-functionalized core–shell structured nanomagnetic Fe3 O4 polymers (TEPA-Fe3 O4 -NMPs) with different amounts of magnetic core were synthesized and fully characterized. The magnetic core might favor mass transfer accelerating the adsorption process. Abstract : A series of tetraethylenepentamine-functionalized core–shell structured nano magnetic Fe3 O4 polymers (TEPA-Fe3 O4 -NMPs) with different amounts of the magnetic core were synthesized and characterized by XRD, EA, VSM, FTIR and XPS. Their applications as adsorbents for phosphate removal from aqueous solutions were studied. The adsorption mechanism and magnetic effects were intensively investigated. The adsorption processes of phosphate by TEPA-Fe3 O4 -NMPs were found to be highly pH dependent and related to the content of Fe3 O4 magnetic core in the adsorbents. The optimized pH value was found to be 3.0 for TEPA-Fe3 O4 -NMPs, while that of TEPA-Fe3 O4 -NMPs-0, which was without the Fe3 O4 magnetic core, was found to be 2.5. Kinetic studies showed that the adsorption of phosphate by TEPA-Fe3 O4 -NMPs followed a pseudo-second-order model, with the adsorption rate constant, k 2, between 0.00274–0.0241 g mg −1 min −1, suggesting a chemisorption process. Activation energies ( E a ) for phosphate removal varied with the content of Fe3 O4 magnetic core, and were found to be 38.9–16.5 kJ mol −1, indicating that the diffusion process might be the rate-controlling step. Thermodynamic studies suggested that the adsorption processes fit the Langmuir isotherm well with the optimized maximum adsorption capacities of phosphate onto TEPA-Fe3 O4 -NMPs obtained when the content of Fe3 O4 in TEPA-Fe3 O4 -NMPs was 14.55%. The Langmuir constants of apparent heat change, K L, were found to be 0.0142–0.0461 L mg −1, and varied with the content of Fe3 O4 magnetic core as well. FTIR and XPS analytical results of the adsorbents before and after phosphate adsorption suggested that phosphate had been successfully adsorbed onto TEPA-Fe3 O4 -NMPs via electrostatic attraction. The existence of the magnetic core might be favorable for mass transfer to accelerate the adsorption process.